FARMERS' PERCEPTIONS OF THE ROLE OF AGRICULTURAL EXTENSION WORKERS IN TENGGARONG SUBDISTRICT KUTAI KARTANEGARA REGENCY EAST KALIMANTAN - Dwijatenaya, Ida Bagus Made Agung; Damayanti, Arista; Ramadhan, Ferdi (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2024)
The agricultural sector, especially rice, is one of the leading sectors, which is very important in helping to support the economy in Kutai Kartanegara Regency. The yields of rice production cannot be separated from the role of agricultural extension workers. Agricultural extension workers certainly play an important role in encouraging changes in the behavior of farmers in order to improve their welfare. This study aimed to determine farmers' perceptions of the agricultural extension workers' role as a dynamic actor, facilitators, and motivators. This research was conducted in Maluhu Village, Tenggarong Subdistrict, Kutai Kartanegara Regency. The data collected is in the form of primary and secondary data. Data was collected through library research, observation, and interviews with the help of questionnaires. The farmer population comes from advanced-class farmer groups totaling 248 people. The number of samples used was determined using the Slovin formula, which consisted of 38 people—aimed at wet rice farmers who were members of the advanced class farmer groups. Selected respondents were determined using the purposive sampling method. The analysis used in this research is a descriptive analysis. The results of this study indicate that farmers' perceptions of the agricultural extension workers' role as a dynamic actor were relatively good. Farmers' perceptions of the role of agricultural extension workers as facilitators and farmers' perceptions of the role of agricultural extension workers as motivators were in a good category. Farmers' perceptions of the role of agricultural extension workers were classified as good, predominantly farmers aged between 50 and 59 years, at elementary school education level, and the size of the land they owned was between 0.25 and 0.5 ha. The analysis showed that farmers' age, education, and land tenure were not correlated with farmers' perceptions of the role of agricultural extension workers as dynamicator, facilitators, and motivators. However, farmer education was significantly correlated, at a 10% error level, to perceptions of the role of extension workers' roles as motivators.